(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
This article centres on the death is sleep metaphor in various (often unrelated) cultures around the world and on the linguistic manifestations of the metaphor in various natural languages. It discusses the physiological and cultural basis for the metaphor and shows how metaphoric thinking shields people around the world from the fear of death. This article also stresses the great power of the death is sleep metaphor and the very real effects it has on human cognition and decision-making – the power which sometimes challenges the supposedly incomplete and inaccurate nature of metaphorical structuring. Finally the article highlights the somewhat unusual synchronic universality and diachronic consistency of the death is sleep metaphor. Namely, as was noted by Kövecses and Radden (1998: 53) and earlier by Turner (1973), Quine (1987), and Pinker (1994), the metaphors and metonymies which are used to hide threatening or unpleasant concepts are often culture specific and the effect they produce is often short-lived. The death is sleep is different in these respects. Probably due to its strong biological and cultural basis the metaphor (and its numerous offshoots and cognates) has survived for centuries and is still very effective in alleviating the negative emotions related to death and dying.